Implementation of Intellectual and Motivating Principle in Training Fundamentals of Philosophy to Students of Art Specialties - Ilkevich, Boris V.; Usmanova, Larisa T.; Ilkevich, Konstantin B. (International Review of Management and Marketing, 2016)
Spatial visualizing ability dominates over conceptual visual thinking in students of art specialties that allows them to achieve high levels of abstraction in the course of creative activity, to specify typical features of artistic images and characters at a philosophical level. Therefore, the necessity to develop students’ of art specialties motivation for highest forms of intelligence arises; awareness of professional and art importance of philosophical education goals promotes this process. In this regard, the paper aims to investigate intellectual-motivating training of students of art specialties in fundamentals of philosophy. The leading research methods were observation, testing, studying of documentation and results of activity, analysis of students’ written creative works; all this allowed to reveal levels of motivation development, students’ progress, and levels of their intelligence development. The obtained results testified to an essential difference in indices of positive dynamics of intelligence, motivation and progress development of students in an experimental group where the authors introduced the program aimed to form motivation to study "Fundamentals of philosophy". The program was developed in compliance with the principle of intellectual motivating training of students of art specialties; students had to fill motivating mind maps promoting the development of their intelligence and motivation for studying philosophy, diagnostics and timely correction of levels of their formation. Materials of the paper are of value for teachers of humanitarian disciplines as part of training competent experts of various profiles. Keywords: Management of Education, Intellectual-Motivating Training, Principle, Students, Future Artists, Fundamentals of Philosophy. JEL Classifications: A23, I23, I26